Developing, Implementing, and Evaluating a Multifaceted Quality Improvement Intervention to Promote Sleep in an ICU. (November 2014) - Kamdar, Biren B.; Yang, Jessica; King, Lauren M.; Neufeld, Karin J.; Bienvenu, O. Joseph; Rowden, Annette M.; Brower, Roy G.; Collop, Nancy A.; Needham, Dale M.
Critically ill patients commonly experience poor sleep quality in the intensive care unit (ICU) because of various modifiable factors. To address this issue, an ICU-wide, multifaceted quality improvement (QI) project was undertaken to promote sleep in the Johns Hopkins Hospital Medical ICU (MICU). To supplement previously published results of this QI intervention, the present article describes the specific QI framework used to develop and implement this intervention, which consists of 4 steps: ( a ) summarizing the evidence to create a list of sleep-promoting interventions, ( b ) identifying and addressing local barriers to implementation, ( c ) selecting performance measures to assess intervention adherence and patient outcomes, and ( d ) ensuring that all patients receive the interventions through staff engagement and education and regular project evaluation. Measures of performance included daily completion rates of daytime and nighttime sleep improvement checklists and completion rates of individual interventions. Although long-term adherence and sustainability pose ongoing challenges, this model provides a foundation for future ICU sleep promotion initiatives.